Night running and night cycling: a review of sociological drivers, health benefits, and their interaction with urban green spaces - Zhang, Jiayi; Yang, Xiaoyu; Peng, Tianhang (Frontiers in Public Health, 2025)
This study investigates the rising trends, sociological drivers, health benefits, and the interaction of night running and night cycling with urban green spaces. Findings indicate that night running and night cycling are mainly driven by increased health awareness, changes in work patterns, social media promotion, and urban economic development. Physiologically, night running and cycling enhance cardiovascular function, alleviate stress, and improve sleep. However, air pollution, inadequate infrastructure, and safety concerns limit the sustainability of these activities. Urban green spaces play a crucial role in promoting nocturnal exercise, with improvements in lighting, safety, and recreational areas due to the growing demand for night fitness. Governments are encouraged to enhance infrastructure and optimize green space planning to foster healthier urban environments.